Serum miR-551b-3p is a potential diagnostic biomarker for gastric cancer - Bai, Su-yang; Ji, Rui; Wei, Hui; Guo, Qing-hong; Yuan, Hao; Chen, Zhao-feng; Wang, Yu-ping; Liu, Zheng; Yang, Xiao-yan; Zhou, Yong-ning (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Gastric cancer (GC) is one of the most common gastrointestinal malignancies. Many studies have demonstrated that serum microRNAs have potential applications as non-invasive biomarkers for cancer diagnosis. The aim of the present study was to investigate the expression of serum miR-551b-3p in patients with GC and to explore its potential as a diagnostic biomarker in GC. Materials and Methods: The expression of miR-551b-3p was detected using quantitative reverse transcription polymerase chain reaction in preoperative serum samples of 50 patients with GC and 53 healthy individuals. An analysis was performed to determine the correlation between serum miR-551b-3p levels and clinicopathological characteristics of patients with GC. The receiver operating characteristic curve was generated, and the cut-off point of serum miR-551b-3p for the diagnosis of GC was selected. The clinical value of serum miR-551b-3p for GC was analyzed by a consistency test. Results: The expression of serum miR-551b-3p was significantly lower in patients with GC than in healthy individuals (p=0.000). Low level was positively associated with tumor size (p=0.014), depth of invasion (p=0.001), and Tumor-Node-Metastasis stage (p=0.022). The area under the curve for serum miR-551b-3p distinguishing patients with GC from healthy individuals was 0.860 (95% CI: 0.787-0.933, p=0.000), with a specificity of 96.2% and a sensitivity of 70%. The kappa consistency test had a kappa value of 0.667 (p=0.000) in GC. Conclusion: Serum miR-551b-3p may potentially serve as a diagnostic biomarker for GC. Cite this article as: Bai S, Ji R, Wei H, et al. Serum miR-551b-3p is a potential diagnostic biomarker for gastric cancer. Turk J Gastroenterol 2019; 30(5): 415-9.